2022
DOI: 10.1186/s13018-022-03293-0
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-rich plasma use in meniscus repair treatment: a systematic review and meta-analysis of clinical studies

Abstract: Background There is conflicting clinical evidence whether platelet-rich plasma (PRP) therapies could translate to an increased meniscus healing rate and improved functional outcomes. The objective of this systematic review and meta-analysis was to compare the failure rate and patient-reported functional outcomes in meniscus repair augmented with and without PRP. Methods We comprehensively searched the PubMed, Web of Science, Medline, Embase, and Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…[24,45] Therefore, many novel techniques were implemented to stimulate meniscus regeneration and to increase the healing capacity after meniscus suture, such as platelet-rich plasma (PRP) and autologous growth factors. [46,47] Although meniscus root tears account for only 10% to 20% of all meniscus tears, “meniscus root tear” was still the research highlight in the field of meniscus suture due to subsequent impairment of meniscus and a study conducted by Allaire demonstrated that medial meniscal root tears are equivalent to subtotal medial meniscectomy. [13,48] Furthermore, meniscus repairs resulted better outcomes in meniscus root tears than other treatments.…”
Section: Discussionmentioning
confidence: 99%
“…[24,45] Therefore, many novel techniques were implemented to stimulate meniscus regeneration and to increase the healing capacity after meniscus suture, such as platelet-rich plasma (PRP) and autologous growth factors. [46,47] Although meniscus root tears account for only 10% to 20% of all meniscus tears, “meniscus root tear” was still the research highlight in the field of meniscus suture due to subsequent impairment of meniscus and a study conducted by Allaire demonstrated that medial meniscal root tears are equivalent to subtotal medial meniscectomy. [13,48] Furthermore, meniscus repairs resulted better outcomes in meniscus root tears than other treatments.…”
Section: Discussionmentioning
confidence: 99%
“…This would aim to improve cellular integration, vascularization, matrix deposition, and inflammation reduction at the meniscus repair site. 8 Notably, the application of PRP, 3 fibrin clots, 4 , 5 marrow stimulation, 6 and MSCs 7 has shown promising results on the basic science level. 13 , 14 , 15 Following repair with biological augmentation, patients have reported significant improvement in functional outcome scores.…”
Section: Discussionmentioning
confidence: 99%
“…Recent efforts have been made to enhance the healing potential of meniscal repairs. Biologic augmentations, such as platelet-rich plasma (PRP), 3 fibrin clots, 4 , 5 marrow stimulation, 6 and mesenchymal stem cells (MSCs), 7 have shown promising results. 8 These interventions have revealed the ability to promote fibrocyte proliferation, extracellular matrix deposition, and neomeniscal tissue formation, highlighting their potential for improving meniscal repair outcomes.…”
mentioning
confidence: 99%
“…Acute symptomatic tears are typically managed conservatively with rest, ice, elevation and oral non-steroidal antiinflammatory medications. Recent research has shown that supervised physical therapy focused on strengthening the muscle groups around the knee (particularly the quadriceps muscles) results in the same clinical outcomes as the most common operation for meniscus tears, an Arthroscopic Partial Meniscectomy (APM) [6][7][8]. Therefore, surgical management of meniscal tears is mostly indicated for patients who don't respond to conservative treatments, have diminished quality of life or have concurrent anterior cruciate ligament injuries.…”
Section: Introductionmentioning
confidence: 99%
“…There is a lack of large-scale clinical evidence demonstrating its efficacy in accelerating healing when administered in conjunction with physical therapy, surgery or both. However, a recent meta-analysis study found that PRP leads to a significant reduction in meniscectomy failure rates and improved overall functional outcomes in patients who received PRP with surgery compared to their non PRP treated counterparts [6].…”
Section: Introductionmentioning
confidence: 99%